2014
DOI: 10.18632/oncotarget.1812
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1R, a target of let-7b, mediates crosstalk between IRS-2/Akt and MAPK pathways to promote proliferation of oral squamous cell carcinoma

Abstract: Insulin-like growth factor (IGF) signaling is involved in oral squamous cell carcinoma (OSCC), but IGF-1 receptor (IGF-1R)-mediated intricate regulatory networks among molecular interactions and signalling path ways in OSCC remain unclear. Here, we found that overexpression of IGF-1R and insulin receptor substrate-2 (IRS-2) was negatively associated with histological differentiation. IGF signaling stimulated OSCC cell growth. Conversely, overexpression of let-7b inhibited proliferation and colony formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…The results indicate that the tumor-inhibitory effect is not solely owing to downregulation of IRS2; other molecules regulated by miR-30a may also contribute to this phenotype. Recent research demonstrated that activated ERK could upregulate the expression of IRS2 (52). Thus, the connection between miR-30a, ERK, and IRS2 raises the possibility that miR-30a targets IRS2, both directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the tumor-inhibitory effect is not solely owing to downregulation of IRS2; other molecules regulated by miR-30a may also contribute to this phenotype. Recent research demonstrated that activated ERK could upregulate the expression of IRS2 (52). Thus, the connection between miR-30a, ERK, and IRS2 raises the possibility that miR-30a targets IRS2, both directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cathepsin B antibody was obtained from D. J. Buttle, University of Sheffield, UK (Buttle et al, 1988). Antibodies against the following proteins were purchased from manufacturers as listed below: actin (Sigma-Aldrich, St. Louis, MO) (Zhou et al, 2005), calnexin (Millipore, Carrigtwohill, Ireland) (Methner and Mayfield, 2010), EGF receptor (Cell Signaling Technologies, Danvers, MA) (Kawahara et al, 2010), Grb-2 (Cell Signaling Technologies) (Benitez et al, 2011), IGF-1R (Cell Signaling) (Michels et al, 2013), IRS-2 (Cell Signaling) (Gao et al, 2014), Lamp-1 (Cell Signaling), LC-3B (Cell Signaling) (Tong et al, 2012), MAPK (Cell Signaling) (Michels et al, 2013), Akt (Cell Signaling), p-IGF-1Rb (Cell Signaling), p-MAPK (Cell Signaling), p-Akt (Cell Signaling) (Michels et al, 2013), p-Shc A (Cell Signaling) (Krall et al, 2011), RAS (Cell Signaling), Shc A (Cell Signaling), N-Shc (BD Biosciences, San Jose, CA) (Tarr et al, 2002). The secondary goat fluor-568 anti-rabbit antibody was from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs are small, noncoding RNAs of 19-25 nucleotides, which regulate physiologic process or pathogenesis by targeting the mRNA to cause transcriptional repression or mRNA degradation (6,7). A number of disruptions in miRNA-target gene regulatory axes in OSCC have been discovered (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%